The Kyoto Protocol and global environmental strategies of the EU, the US and Japan: A perspective from Japan - Tatsuyoshi Saijo (Osaka University, Institute of Social and Economic Research (ISER), 2001)
Despite the objection of the Bush administration to the U.S.'s ratification of the Kyoto Protocol, its entry into force has come to be realistic due to the Bonn Agreement in July. The purpose of this paper is first to survey the framework of the Protocol, and then to analyze the strategic positions of the EU, the U.S., and Japan in negotiations for designing the details of the Protocol. Finally, this paper intends to consider the due strategy of Japan, as well as to identify the problems of the Protocol, which will be a help for designing a new framework that will enable the participation of developing countries.
Keywords: 330; Umweltabkommen; Internationale Klimapolitik; Internationale Umweltpolitik; EU-Staaten; USA; Japan